Postmodernisme Dalam Pengembangan Wacana Formulasi Kebijakan - Gabriel Lele (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 1999)
The currently well-established study of policy-making has been recultant to accept the contribution of post-modernist's point of view, even though' the state of the art of study is prone to numerous criticism. This article argues that the on going attempt to reorient of the role of the state would be conducive for the postmodernist perspective in policy-making, especially policy formulation.